Bakhtiniana e o compromisso ético com a produção da ciência - Brait, Beth; Cruz Pistori, Maria Helena; Lopes, Bruna; Stella, Paulo Rogério; Godinho de Alcântara, Regina; Pucci Faria Penteado e Silva, Adriana; Gontijo Rosa, Carlos (Bakhtiniana. Revista de Estudos do Discurso, 2025)
Editorial 20.2